Parenting Styles and Parental Self-Efficacy in Parents of Children with Neurological Disorders - Ioana Elena Cioca; Maria-Veronica Morcov; Corina Sporea; Oana Alina Apostol; Cristian-Gabriel Morcov; Marian Ghita; Angelo Pellegrini; Elena-Nicoleta Bordea (Balneo and PRM Research Journal)
This study examines the influence of different parenting styles on parental self-efficacy in families with children diagnosed with neurologic disorders. Specifically, it explores the correlation between five distinct styles—authoritarian, authoritative, permissive, perfectionist, and uninvolved—and parental confidence in managing the challenges associated with raising children with disabilities. The study involved 134 parents of children with neurologic disorders and was conducted in a specialized medical rehabilitation center for children in Bucharest, Romania. Data was collected using the Parenting Style Questionnaire (PSQ) and the Brief Parental Self-Efficacy Scale (BPSES). Statistical analyses were performed using Spearman's rank-order correlation coefficient (Spearman's rho) to assess monotonic relationships, complemented by nonlinear regression modeling to evaluate predictive associations. The results showed statistically significant correlations between parenting styles and self-efficacy across genders and educational levels. Moderate negative correlations were found between self-efficacy and the authoritarian parenting style for both men (p < 0.001, r = -0.581) and women (p < 0.001, r = -0.519). A moderate positive correlation was observed between self-efficacy and the authoritative parenting style for women (p < 0.001, r = 0.525). Furthermore, self-efficacy was moderately negatively correlated with the authoritarian parenting style for parents with university education (p < 0.001, r = -0.601) and pre-university education (p < 0.001, r = -0.530). Regression analysis indicated that authoritarian parenting was a significant predictor of diminished parental self-efficacy, explaining 32.7% of the variance in parental self-efficacy outcomes. The findings suggest that understanding the impact of parenting styles on self-efficacy is crucial for designing targeted interventions to improve parental confidence, particularly for families raising children with neurologic disorders. Parental self-efficacy may be increased by intervention programs that encourage authoritative parenting techniques while lowering authoritarian inclinations. For kids with neurological diseases, this can therefore result in better coping strategies, enhanced parent-child relationships, and better developmental and psychological results.